Equality Arguments, Contemporary Feminist Voices and the Matrimonial Causes Act 1923. Issue 2 (4th May 2022) - Hamilton, Frances
ABSTRACT: The Matrimonial Causes Act 1923 equalized the grounds for divorce for men and women, removing the prior existing double standard. Before this reform whilst husbands could divorce wives on the basis of adultery alone, wives had to prove additional aggravating factors. This author by analysis of primary sources from the National Union of Societies for Equal Citizenship archive, Hansard and the Royal Commission on Divorce and Matrimonial Causes Report 1912 demonstrates that some contemporaneous actors were persuaded by the symbolism of equality arguments and considered these convincing reasons for reform. This led to the enactment of the legislation in question. Yet in critical evaluation other feminists already recognized limitations with the reform achieved. Namely, that it distracted from other agendas, took too long, that poverty remained a barrier to reform and the reform achieved did not go far enough as the grounds for divorce were not reformed and there was no genuine commitment to equality for women within marriage. Others were prepared to adopt any strategy which led to reform seeing this as pragmatic first step.